Molecular Mechanisms of the Antiatherogenic Action of Adiponectin - Kobayashi, Kunihisa; Inoguchi, Toyoshi (Vascular Disease Prevention (Discontinued), 2007)
Recently, many investigators have reported that adipocytes secrete a variety of bioactive substances, termed adipokines (adipocytokines), including tumor necrosis factor alpha (TNFα), interleukin-6 (IL-6), leptin, resistin, adiponectin and so on. Adiponectin is most abundant in the plasma and produced exclusively by adipocytes. This adipokine has been reported to be an exciting player in the field of energy homeostasis regulation. Furthermore, adiponectin has been shown to have antiatherogenic properties in epidemiological, in vitro and in vivo studies. This review summarizes the currently available information regarding this important biomolecule and discusses its feasibility for the treatment of atherosclerotic diseases.
Keywords: adiponectin